A novel disorder of sex development, characterized by progressive regression of testicular function and cystic leukoencephalopathy. Issue 3 (4th February 2017) - Rossi, Massimiliano; Vasiljevic, Alexandre; Labalme, Audrey; Dijoud, Frédérique; Mallet‐Motak, Delphine; Petcu, Carmen Adina; Touraine, Renaud; Vianey‐Saban, Christine; Guibaud, Laurent; Edery, Patrick; Sanlaville, Damien; Morel, Yves
Abstract : We report a novel syndromic disorder of sex development observed in three male siblings, presenting with the association of micropenis without hypospadias, cryptorchidism, very low level of antimüllerian hormone in the neonatal period, and no persistent müllerian duct structures, suggesting a progressive regression of testicular function. The patients described here showed a striking neurological involvement including bilateral periventricular cysts observed in the anterior part of the frontal horns prenatally and increasing in size and number over time, associated with infra and supratentorial parenchymal atrophy, dilated ventricular system, corpus callosum hypoplasia, severe intellectual disability, and epilepsy. Associated features included a distinctive facies, joint contractures, retinopathy, and hearing loss. Pathological examination was consistent with testicular dysgenesis and leukoencephalopathy with spongiosis and microcalcifications. To the best of our knowledge, this disease, characterized by a recognizable pattern of malformations, has not been previously reported. An exhaustive genetic and metabolic evaluation was normal. Autosomal recessive inheritance was considered to be likely, on the basis of SNP studies. We hope that the detailed description provided here of the clinical, radiological, and pathological findings observed in this family will help to identify further unrelated patients, and ultimately, to clarify the genetic basis of this condition. © 2017 Wiley Periodicals, Inc.